ANALISIS STRATEGI PENGEMBANGAN USAHA PETERNAKAN BABI DI KABUPATEN MIMIKA(Studi Kasus Di Kelurahan Kamoro Jaya Distrik Wania) - Lora Monica BR Ginting M; Stepanus Sandy (CV. ADIBA AISHA AMIRA, 2023)
This study aims to determine the strategy for developing a pig farming business in Mimika Regency (a case study in Kamoro Jaya Village, Wania District). Research on pig farming business development strategies in Mimika Regency (a case study in Kamoro Jaya Village, Wania District) was carried out using descriptive research methods. The data collection tool used in this study is a questionnaire (questionnaire). The data were analyzed using SWOT analysis. The results of this study indicate that the strategy for developing a pig farming business in Kamoro Jaya Village, Wania District, Mimika Regency has high strengths and opportunities. Which is the strength factor at 3.76 (internal) and opportunity at 3.70 (external). The business development strategy for pig farms is using the Strong Opportunity strategy, namely increasing livestock production to anticipate the high demand for pork, taking advantage of current business conditions to gain the trust of bank loans and building partnerships with related agencies in providing counseling or training on how to manage livestock and the marketing